2011
DOI: 10.1371/journal.pone.0021828
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Specific Cumulative Incidence of Infection with Pandemic Influenza H1N1 2009 Was Similar in Various Countries Prior to Vaccination

Abstract: BackgroundDuring the influenza pandemic of 2009 estimates of symptomatic and asymptomatic infection were needed to guide vaccination policies and inform other control measures. Serological studies are the most reliable way to measure influenza infection independent of symptoms. We reviewed all published serological studies that estimated the cumulative incidence of infection with pandemic influenza H1N1 2009 prior to the initiation of population-based vaccination against the pandemic strain.Methodology and Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 50 publications
(121 reference statements)
8
70
1
2
Order By: Relevance
“…Our results are consistent with our estimates of H1N1pdm seroprevalence using post‐pandemic sera and with other H1N1pdm seroprevalence studies recently or not yet published from Iceland, Mexico, Chinese Taipei, India, Mongolia, Mali,53, 54, 55, 56, 57 Laos, Djibouti, and Bolivia (CoPanFlu‐International consortium unpublished data, personal communication from X. de Lamballerie), with a study from Greece with pre‐ and post‐pandemic sera that was excluded from our analyses51 but are slightly higher than the overall estimated cumulative incidence found in one analysis 17. This may be because our study includes a number of additional middle and low countries who conducted serologic studies because this analysis was published and because we excluded studies which focused on specialized populations17).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our results are consistent with our estimates of H1N1pdm seroprevalence using post‐pandemic sera and with other H1N1pdm seroprevalence studies recently or not yet published from Iceland, Mexico, Chinese Taipei, India, Mongolia, Mali,53, 54, 55, 56, 57 Laos, Djibouti, and Bolivia (CoPanFlu‐International consortium unpublished data, personal communication from X. de Lamballerie), with a study from Greece with pre‐ and post‐pandemic sera that was excluded from our analyses51 but are slightly higher than the overall estimated cumulative incidence found in one analysis 17. This may be because our study includes a number of additional middle and low countries who conducted serologic studies because this analysis was published and because we excluded studies which focused on specialized populations17).…”
Section: Discussionmentioning
confidence: 69%
“…This study builds upon the findings of Kelly et al 17. by including a number of additional H1N1pdm serologic studies conducted from a number of additional countries since this publication.…”
Section: Introductionmentioning
confidence: 80%
“…It is noteworthy that a recently published study,2 which compared many sero‐epidemiological surveys published after the 2009 pandemic, suggests that CI calculations based on the binomial distribution led to underestimation of the uncertainty associated with estimates of the cumulative incidence of infection. However, the overall conclusions remain the same.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission, case‐fatality and hospitalization rates can only be evaluated when the true incidence of infection is assessed, based on sero‐epidemiological studies. A recent review concluded that exposure to the virus based on comparison between seroprevalence in samples collected before and after the pandemic was highest in children and teenagers reaching 16–43% globally 2. Pre‐pandemic seroprevalence was highest in age‐groups >60 years 1…”
Section: Introductionmentioning
confidence: 99%
“…The H1N1 influenza virus (also referred to as "swine flu") infected an estimated 11% to 18% of the population (Kelly et al, 2011). Mexico was at the centre of the pandemic, being among the first countries where swine flu was detected and also where mortality rates were reportedly higher than those in many other countries (Echevarría-Zuno et al, 2010).…”
Section: Influenza Vaccination For Older Peoplementioning
confidence: 99%